Propuesta metodológica de formulación de proyectos en municipios de sexta categoría para el acceso a recursos provenientes de programas de mejoramiento de vivienda de nivel central: Caso de estudio municipio el Espino, Boyacá (2019)
Sixth-grade municipalities are characterized by a lack of resources and a high dependence on the transfers of the nation both for its operation and for the implementation of social policies to reduce the high rates of basic needs Unsatisfied, therefore the central government destines resources to meet the housing needs of all the municipalities of the country, however there are a number of requirements that the territorial entities offering housing improvement projects They must comply at the time of structuring the projects and since the granting entities evaluate the projects according to these specific characteristics it is necessary that these are established under these guidelines; Based on the previous considerations and the financial reality of the sixth-grade municipalities, it is possible that the territorial entities that are not able to manage and structure these projects, therefore are not chosen and finally do not They can cope with the existing needs in their population on issues related to housing deficits.